Experimental Analysis of Plantar Fascia Mechanical Properties in Subjects with Foot Pathologies - Todros, Silvia; Biz, Carlo; Ruggieri, Pietro; Pavan, Piero G. (Applied sciences, 2021)
Plantar Fascia (PF) is a fibrous tissue that plays a key role in supporting the foot arch; it can be affected by several pathologies that can alter foot biomechanics. The present study aims at investigating the mechanical behavior of PF and evaluating possible correlations between mechanical properties and specific pathologies, namely diabetes and plantar fibromatosis (Ledderhose syndrome). PF samples were obtained from 14 human subjects, including patients with Ledderhose syndrome, patients affected by diabetes and healthy subjects. Mechanical properties of PF tissues were evaluated on three samples from each subject, by cyclic uniaxial tensile tests up to 10% of maximum strain and stress relaxation tests for 300 s, in hydrated conditions at room temperature. In tensile tests, PF exhibits non-linear stress–strain behavior, with a higher elastic modulus (up to 25–30 MPa) in patients affected by Ledderhose syndrome and diabetes with respect to healthy subjects (elastic modulus 10 ÷ 14 MPa). Stress-relaxation tests show that PF of patients affected by Ledderhose syndrome and diabetes develop more intense viscous phenomena. The results presented in this work represent the first experimental data on the tensile mechanical propertied of PF in subjects with foot diseases and can provide an insight on foot biomechanics in pathological conditions.